Community Empowerment through the Creative Economy for the Realization of Sustainable Economic Self-Reliance Based on Islamic Values at the Sanggar Batik Selaras Pinang Masak, Jambi - Mutia, Agustina; Hassanee, Narong; Rahma, Sri; Nofriza, Eri; Fusfita, Nurlia; Hamzah, Maulana; Hidayat, Angger; Hermanda, Azzahra Puan; arzmi, Muhammad riski (PT Inovasi Pratama Internasional, 2025)
This article aims to describe the process and outcomes of community empowerment at the Sanggar Batik Selaras Pinang Masak in Jambi through the development of a creative economy underpinned by Islamic values. This batik center represents a crucial hub for the preservation of local culture and economy, yet it faces significant challenges concerning product innovation, digital marketing, and the consistent application of Sharia business ethics. The methodology employed is Participatory Action Research (PAR), which actively involved the participation of artisans and management in every stage: planning, action, observation, and reflection. The action phase encompassed digital marketing training, a workshop on Islamic business ethics, and mentorship for the formulation of Sharia-based Standard Operating Procedures (SOP). The results demonstrate a significant increase in the understanding and proficiency of digital marketing, alongside a stronger commitment to implementing Islamic principles such as honesty (shiddiq), trustworthiness and professionalism (amanah), and justice (‘adl) in all transactions and production processes. This empowerment initiative not only enhances the potential for the center's sustainable economic self-reliance but also reinforces the cultural and spiritual identity of the artisan community.